1992
DOI: 10.7326/0003-4819-117-10-824
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Gastroesophageal Reflux to Chest Pain in Patients with Coronary Artery Disease

Abstract: Gastroesophageal reflux disease is a common, treatable cause of chest pain in patients with coronary artery disease who have atypical symptoms and remain symptomatic despite aggressive antianginal therapy. Combined Holter and 24-hour esophageal pH studies are complementary investigations for elucidating the cause of chest pain in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 26 publications
2
47
0
3
Order By: Relevance
“…16 Although the omeprazole test has been shown to be an accurate diagnostic test, the duration of treatment and the optimal dose remain issues of controversy in the literature. Some authors [17][18][19] suggested that 6 to 8 weeks of treatment is necessary for diagnostic accuracy. However, it is impractical and expensive to have patients complete a full 2 months of antireflux treatment before it is determined whether the medication is of benefit.…”
Section: Commentmentioning
confidence: 99%
“…16 Although the omeprazole test has been shown to be an accurate diagnostic test, the duration of treatment and the optimal dose remain issues of controversy in the literature. Some authors [17][18][19] suggested that 6 to 8 weeks of treatment is necessary for diagnostic accuracy. However, it is impractical and expensive to have patients complete a full 2 months of antireflux treatment before it is determined whether the medication is of benefit.…”
Section: Commentmentioning
confidence: 99%
“…In one study, chest pain evaluated by cardiologists was clinically misdiagnosed as cardiac disease in 25% of patients (17). A number of previous studies have provided evidence that the reflux prevalence is over 40% in patients with CAD, with 40-70% of cases of reflux being directly associated with chest pain symptoms (18)(19)(20)(21)(22)(23). However, this study is the first to investigate acid reflux in patients with CAD and refractory chest pain.…”
Section: Discussionmentioning
confidence: 89%
“…Lux et al showed that 57% of patients with CAD have chest pain correlated with acid reflux (20). Singh et al investigated symptomatic coronary patients and found that 41% of such patients have acid reflux (21).…”
Section: Discussionmentioning
confidence: 99%
“…Pacientes com refluxo esofagiano podem apresentar desconforto torácico, geralmente em queimação (pirose), mas que às vezes é definido como uma sensação opressiva, localizada na região retroesternal ou subesternal, podendo se irradiar para o pescoço, braços ou dorso, às vezes associada à regurgitação alimentar, e que pode melhorar com a posição ereta ou com o uso de antiácidos, mas também com nitratos, bloqueadores dos canais de cálcio ou repouso [41][42][43] . A dor da úlcera péptica geralmente se localiza na região epigástrica ou no andar superior do abdômen mas às vezes pode ser referida na região subesternal ou retroesternal.…”
Section: Causas De Dor Torácica E Diagnóstico Diferencialunclassified